Peningkatan Layanan Pendidikan Anak-Anak Melalui Program Bimbingan Belajar Di Desa Batu Gana - Imbalo Hasibuan; Peri Irawan; Anisa Sabila; Cahaya Cahaya; Hidia Fitri; Iqrima Sahuro; Mhd Ilham Nasution; Rosila Rosila; Vivit Felia Putri; Ali Jusri Pohan (Pusat Riset dan Inovasi Nasional, 2024)
Students are not only required to be able to memorize but also have to understand and be interested, because if children are interested in the lesson they will naturally find out what they don't know. For this reason, learning using the learning while playing method is implemented so that it can motivate students in learning to become more creative individuals and also active in thinking and solving problems. Tutoring plays a very important role in children's learning development, because what children get is not only from school, with tutoring it can help children's difficulties while at school. Non-formal education is expected to increase students' interest or interest in learning. In non-formal education, students are invited to learn using different methods to formal education in general, non-formal education is more relaxed and fun by introducing something new or interesting things that they don't understand, different from formal education, learning is more fun by playing games. on the sidelines of learning when the child seems to be getting bored with learning.